Perforation of the Pregnant Uterus during Laparoscopy for Suspected Internal Herniation after Gastric Bypass - T. Mala; N. K. Harsem; S. Røstad; L. C. Mathisen; A. F. Jacobsen (Case Reports in Obstetrics and Gynecology)
We report perforations of a pregnant uterus during laparoscopy for suspected internal herniation after gastric bypass at 24 weeks of gestation. Abdominal access and gas insufflation were achieved by the use of a 12 mm optic trocar. An additional 5 mm trocar was positioned. The perforations were handled by suturing following laparotomy and mobilisation of the high located uterus. The uterine fundus was located in the subcostal area. Internal herniation was not verified. A cesarean section was made 6 weeks later due to acute low abdominal pain. During delivery the uterus was found normal. At 5 months of age the child has developed normal and seems healthy. Optical trocars should be used with caution for abdominal access during laparoscopy in pregnancy. Open access should probably be preferred in most cases. Accidental perforations of the uterine cavity may be handled in selected cases with simple closure even following the use of large trocars under close postoperative surveillance throughout the pregnancy.